The effect of liquidity shocks on the bank lending channel: Evidence from India - Mishra, A.; Burns, Kelly (Elsevier, 2017)
Â© 2017 Elsevier Inc. Using a structural VAR framework and unique bank liquidity index, this study builds a short run model to analyse dynamic interactions among monetary policy, bank liquidity, and bank lending in India. We find that monetary policy shocks have strong initial and persistent impacts on bank lending, while liquidity shocks impact bank lending after a 9-month lag. We also find evidence of an indirect feedback channel between monetary policy and bank lending operating through changes in bank liquidity. However, the indirect effect of monetary policy on bank lending (through bank liquidity) operates with a lag of roughly 6â€“9 months.